Atención al cliente en el Local Comercial “Mindiola” de la ciudad de Babahoyo, periodo 2023. - Bolaños Mindiola, Adamarys Maithe (2024)
This work focused on the search for a problem in the “Mindiola” Commercial Premises. The various areas of improvement in the quality of customer service were evident. Although the relevance of courtesy and assistance to customers is recognized, the owner's admission of complaints suggests failures in customer service management. The lack of a complaint resolution channel and the need to improve the knowledge and work of the customer service team highlighted the need to establish a key structure to improve customer loyalty. The objective of building customer loyalty is to provide a comprehensive approach that includes all aspects of the customer experience, including incentives so that the customer is satisfied with their service, increasing trust and loyalty. As well as it was recommended to implement a systematic and continuous training program for employees, conflict resolution and effective communication. These discoveries provide a solid basis for making decisions, identifying priority areas for improvement and designing specific strategies to address them within the “Mindiola” Commercial Premises.